Psychological and behavioral assessment in children with treated hypothyroidism using developmental psychopathology checklist scale - Singh, Poonam; Chaudhari, Falguni; Deshpande, Ujjwala; Saliya, Maulik (Indian Journal of Child Health, 2018)
Objectives: The objectives of the study were to assess psychological and behavioral problems in treated hypothyroid children with euthyroid status, with the help of developmental psychopathology checklist (DPCL). Materials and Methods: This was an observational comparative study done in pediatric endocrinology clinic in a medical college over 6 months. 20 consecutive hypothyroid patients between 5 and 15 years with euthyroid status were compared to 20 controls for psychosocial problems using DPCL scale. The DPCL scale identifies the following clusters of abnormal developmental history, developmental problems/disorders, emotional disorders, attention deficit hyperactivity, childhood psychosis, learning disorder, somatic problems, conduct disorder, autism, and obsessive-compulsive neurosis. Results: All cases had at least 1 cluster affected. The most common clusters affected were emotional disorders in 85% cases, abnormal developmental history in 80%, developmental problems in 75%, attention deficit hyperactivity (ADHD) in 70% cases, and learning disorders in 70% cases. Among males, the common problems were abnormal developmental history (86%), developmental problems (86%), ADHD (86%), emotional disorder (86%), and learning disorder (71.43%). In females, problems noted were an emotional disorder (84%), abnormal developmental history (86%), developmental problems (69%), learning disorder (69%), and ADHD (61%). This difference in cluster affection in males and females was not statistically significant. Single domain affection was found in 10% of patients, but more than 5 domain affections were seen in 60% of patients, and this was highly significant. Conclusion: Even with the euthyroid state in hypothyroidism, psycho-behavioral problems are common in children.